RFID tag aided navigation system for lawnmowers - Costa, Dany dos Santos (2023)
Bosch Indego is an autonomous lawnmower that uses a perimeter wire to define the mowing area as well as a basic location/navigation mechanism. Apart from this absolute reference, the robot’s only sources of data are their inertial sensors and the integration of the motor’s movement (odometry). This implies that in larger gardens, there may be significant deviations, resulting in miscuts in certain regions. The main objective of this dissertation is to demonstrate that by integrating RFID tags placed on the grass as new reference points, it is possible to optimize the navigation/location process and reduce the robot’s localization deviation without having to return to the only source of absolute location (dock), which may be too far away from the cutting zone. Firstly, a research was conducted to determine the sort of RFID system that would be most suited for this application. Following that, it was implemented a system capable of proving the capacity to georeference RFID tags validating the relative error between the tag and the robot’s location with an emulator designed for this purpose. Subsequently, several tests were carried out on two synthetic fields, where tags were placed on the grass either randomly or in the perimeter wire. In the end, it was demonstrated that an RFID system can be implemented with the potential of aiding the mower by providing more reference points to the area. However, tests showed that the best solution is based on the implementation of tags exclusively on the perimeter wire, since the robot’s movement is very unpredictable, making it not always possible to correctly detect the tags. This does not happen when the mower is following the perimeter wire. Even so, it was possible to exemplify the great versatility that an RFID system can offer, namely being able to identify the dock without user intervention. Future work on this system should focus on improving tag detection accuracy as well as tag positioning relative to robot movement.